Association and Path Coefficient Analysis Studies in Potato (Solanum tuberosum L.) Genotypes at Adet, Northwestern Ethiopia: - - Zeleke, Awoke Ali; Getahun, Baye Berihun (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during main rain fall season from June to October, 2018 in Adet, Ethiopia with the objective of estimating the correlation and identifying the direct and indirect effect of yield contributing traits on potato crop. 36 potato genotypes were evaluated in simple lattice design in two replications. The analysis of variance revealed that highly significant (p<0.001) difference among potato genotypes for all traits except average stem number. Total tuber yield was positively correlated with days to maturity, plant height, average stem number, marketable, unmarketable, total tuber number and marketable yield while it was negatively correlated with late blight severity percentage at both phenotypic and genotypic level. High correlation was observed between total tuber yield and marketable tuber yield (rp=0.982 and rg=0.986) followed by total tuber number (rp=0.735 and rg=0.789), and marketable tuber number (rp=0.700 and rg=0.737). Days to flowering, days to maturity, average stem number, marketable and unmarketable tuber number, starch content percentage, average tuber weight, and unmarketable tuber yield had positive direct effect on the total tuber yield at both genotypic and phenotypic level. Highly direct effect on total tuber yield was observed by marketable and unmarketable tuber number (3.65 and 1.17 respectively) and average tuber weight (0.56). Therefore, traits with significant positive correlated and direct effect on total tuber yield such as days to maturity stem number, marketable tuber number, marketable tuber yield and average tuber weight should be considered in selection criteria for enhancing tuber yield in potato.